Pengaruh Media Sosial Instagram Terhadap Fanatisme dan Fomo Pada Followers Akun Instagram @7fanboy.Bts Army Indonesia - Vinny Amanda; Nurjanah Nurjanah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The development of communication technology is now inseparable from the internet. Information and communication technology has become very fast especially with the addition of the internet so that it has experienced many changes such as the emergence of online media that makes it easier for humans to access all information and content without limit. One of the phenomena of the influx of new culture due to globalization and the internet is Hallyu or K-Pop. Social media has become a place that really helps K-Popers in accessing all sources of information about their idols, not only as a means of information, social media also acts as a medium of communication for them with their favorite idols. This research uses the basis of Media Dependence Theory (Dependency Theory). This study aims to determine how much influence Instagram social media has on fanaticism and FoMO on the